A LINDB e o Direito Tributário: um estudo acerca da aplicação do Artigo 24 em Matéria Tributária - Oliveira, Bruno Santos Lins de (2020)
This paper aims to analyze the application in tax law of Article 24 of Decree-law nº. 4.657/42, the “Law of Introduction to the Norms of the Brazilian Law”. Theme that has been quite recurrent in administrative tax judgments and that has aroused debates, especially since most decisions have understood by its inapplicability in the matter of taxes, under the most diverse grounds, with emphasis on those that give character of excessive speciality to tax law. Thus, what is intended is a scientific analysis of the foundations and content of the aforementioned article 24, whose intention is to increase efficiency in the application and interpretation of legal norms, more specifically when it comes to the protection of Legal Certainty in case of the modification of the previous majority understanding. that guided the behavior of individuals. For this purpose, the “Constructivismo lógico-semântico” theory will be used as a method, due to its technical and analytical precision for the study of linguistic legal phenomena such as the interpretation and application of legal norms